2023
DOI: 10.1007/s13178-023-00800-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disparities Between Lesbian Mothers and Heterosexual Parents: the Mediating Role of Positivity

Abstract: Introduction Previous evidence has shown better mental health outcomes for lesbian mothers, in comparison with heterosexual parents. The present study explored the mediating role of positivity (i.e., the tendency to view life with a positive outlook) in determining these mental health differences. Methods Seventy-two Israeli lesbian mothers by donor insemination (from 36 families) were compared with 72 Israeli heterosexual parents by assisted reproduction (without donated gametes; from 36 families) on positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…In the present study, Cronbach’s α was .81. The POS has been used in previous studies with parents with minoritized sexual identities (see, e.g., Shenkman, Bos, et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, Cronbach’s α was .81. The POS has been used in previous studies with parents with minoritized sexual identities (see, e.g., Shenkman, Bos, et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some studies have even revealed that preschool and school-age children of lesbian and gay parents exhibit better psychological adjustment compared to both normative scores (Carone, Lingiardi, et al, 2018; Green et al, 2019) and their counterparts in heterosexual parent families (Baiocco et al, 2018; Shenkman, Carone, et al, 2023). Similarly, research has found that lesbian and gay parents tend to show higher parenting quality and better mental health, relative to heterosexual parents (Bos & Gartrell, 2020; D’Amore et al, 2023; Shenkman, Bos, et al, 2023).…”
mentioning
confidence: 98%
See 1 more Smart Citation